Ägyptologiegeschichte digital: Bericht über ein DFG-Projekt zur Erschließung und Digitalisierung des Nachlasses von Adolf Erman in der SuUB Bremen - Hermes-Wladarsch, Maria (Zeitschrift für ägyptische Sprache und Altertumskunde, 2021)
Adolf Erman is one of the founders of modern Egyptology. His life and achievements are deeply connected with the changes in this field, which starting as a romanticized activity and turned into a modern discpline. His extensive correspondence is as important for the history of Egyptology as it is for the general history of science. Because of family connections, Adolf Erman’s estate was almost completely bequeathed to the Bremen State and University Library. Between 2019 and 2021, the whole estate has been described and digitized in a project funded by the German Research Foundation (DFG). The paper describes the estate, its digitization and the range of its possible usage.